Destabilization of mutualistic interactions shapes the early heat stress response of the coral holobiont - Emma Marangon; Nils Rädecker; Joan Y. Q. Li; Marko Terzin; Patrick Buerger; Nicole S. Webster; David G. Bourne; Patrick W. Laffy (Microbiome)
Abstract Background The stability of the symbiotic relationship between coral and their dinoflagellate algae (Symbiodiniaceae) is disrupted by ocean warming. Although the coral thermal response depends on the complex interactions between host, Symbiodiniaceae and prokaryotes, the mechanisms underlying the initial destabilization of these symbioses are poorly understood. Results In a 2-month manipulative experiment, we exposed the coral Porites lutea to gradually increasing temperatures corresponding to 0–8 degree heating weeks (DHW) and assessed the response of the coral holobiont using coral and Symbiodiniaceae transcriptomics, microbial 16S rRNA gene sequencing and physiological measurements. From early stages of heat stress (< 1 DHW), the increase in metabolic turnover shifted the holobiont to a net heterotrophic state in which algal-derived nutrients were insufficient to meet host energy demands, resulting in reduced holobiont performance at 1 DHW. We postulate the altered nutrient cycling also affected the coral-associated microbial community, with the relative abundance of Endozoicomonas bacteria declining under increasing heat stress. Integration of holobiont stress responses correlated this decline to an increase in expression of a host ADP-ribosylation factor, suggesting that Symbiodiniaceae and Endozoicomonas may underlie similar endosymbiotic regulatory processes. Conclusions The thermotolerance of coral holobionts therefore is influenced by the nutritional status of its members and their interactions, and this identified metabolic interdependency highlights the importance of applying an integrative approach to guide coral reef conservation efforts. Video Abstract